2015
DOI: 10.1007/s00004-015-0276-2
|View full text |Cite
|
Sign up to set email alerts
|

Oracular Functioning and Architecture of Five Ancient Apollo Temples Through Archaeoastronomy: Novel Approach and Interpretation

Abstract: Five temples of Apollo on Mainland Greece and Ancient Ionia (Asia Minor), namely Delphi, Didyma, Hierapolis, Delos and Rhodes, have been examined regarding their functioning through astronomical orientation. Recent research has shown that the rise, setting, orbit and observation of certain constellations in the celestial sphere, as well as the solar stands, can be directly related to the architecture of the temple, i.e. construction, orientation, and keeping a calendar of the most important Apollonian oracular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…One key example, which is relevant in our context, is that of the Greek temples. From a general-and vague-notion that "most Greek temples face the rising sun", studies have turned to analysing specific orientations to connect them to specific deities, sacred attributes, and rites [17][18][19][20][21][22]. It is our aim here to approach the problem of the archaeoastronomy in the Bekaa valley exactly in the same way, so that-for instance-vague statements such those present in many publications on Baalbek where it is noticed that the Temple of Jupiter "opens to the east" as alleged proof of the solar character of the deity can be overcome by a rigorous analysis.…”
Section: Orientations Of the Temples Of The Bekaa Valleymentioning
confidence: 99%
“…One key example, which is relevant in our context, is that of the Greek temples. From a general-and vague-notion that "most Greek temples face the rising sun", studies have turned to analysing specific orientations to connect them to specific deities, sacred attributes, and rites [17][18][19][20][21][22]. It is our aim here to approach the problem of the archaeoastronomy in the Bekaa valley exactly in the same way, so that-for instance-vague statements such those present in many publications on Baalbek where it is noticed that the Temple of Jupiter "opens to the east" as alleged proof of the solar character of the deity can be overcome by a rigorous analysis.…”
Section: Orientations Of the Temples Of The Bekaa Valleymentioning
confidence: 99%
“…Delphinus is indeed one of the constellations connected to Apollonian mythology. According to a recent proposal, it was even used as a marker for the season of the pilgrimage to Delphi [11], although the faintness of the constellation casts doubts on its practical calendrical use [4] and other, brighter constellations, Lyra and Cygnus, were more tightly connected with this God [11].…”
Section: The Temple Of Junomentioning
confidence: 99%
“…His work pioneered research on the Archaeology of the Landscape, pursuing the idea that landscape and temples formed an architectural unit that was characterized in accordance with the specific god worshipped. Occasionally, the choice of the terrain and/or of the landscape was exploited to achieve a specific orientation, while in other cases the temple architecture in itself created the sacred landscape [4]. In any case, the matter of understanding the specific orientation of the Greek temples deserves to be dealt with on its own.…”
Section: Introductionmentioning
confidence: 99%
“…71-95). Other authors, such as Ioannis Liritzis and Belén Castro, have suggested the Lyra and Cygnus constellations were related to the oracle consultation (Liritzis and Castro 2013;Castro et al 2016), somehow reflecting Boutsikas' main argument given the vicinity of the three asterisms. In contrast, Tomislav Bilić has discussed the northwards journey of Apollo in relation to the course of the Sun (Bilić 2012(Bilić , 2021.…”
mentioning
confidence: 97%